Erratum to "Efficient processing of moving top-k spatial keyword queries in directed and dynamic road networks" (Wireless Communications and Mobile Computing, (2018) 2018 (19) DOI: 10.1155/2018/7373286) - Attique, Muhammad; Cho, Hyung Ju; Chung, Tae Sun (Wireless Communications and Mobile Computing, 2019)
In the article titled "Efficient Processing of Moving Top-k Spatial Keyword Queries in Directed and Dynamic Road Networks" [1], there was an error in the number of the only lemma, where Lemma should be corrected to Lemma 1.